High-Performance Work System and Employee Counterproductive Work Behavior: The Perspective of Employee Perception - Ling Peng; Jiafu Su; Yupei Du; Muzi Li (Complexity)
Employee counterproductive work behavior (ECWB) in the workplace has caused serious harm to the organization, and its recessive occurrence creates difficulty for the organization to guard against it. This study aims to explore the influence of high-performance work systems (HPWS) on the two sides of ECWB with employees and the internal influence path. It also aims to combine resource conservation and affective events theories to build an HPWS five-level model. It provides human resource management measures for enterprises to reduce and prevent the ECWB effectively. This study adopts a quantitative analysis method to conduct a questionnaire survey among employees in 366 enterprises in China. The results show that HPWS has a significant two-sided impact on ECWB. For employees with positive emotions, HPWS improved employee performance and inhibited ECWB. Meanwhile, for employees with negative emotions, HPWS reduces employees’ work input and increases employees’ counterproductive behaviors. For negative employees, the positive effect of HPWS is more significant than the negative effect of positive employees. In addition, organizational commitment has a moderating effect on the counterproductive behavior of negative employees. Therefore, when implementing HPWS, enterprises should consider the impact of both sides of HPWS on ECWB and adopt a more humane management method. In this study, a practical five-level HPWS model is constructed, which complements the existing research model and provides a theoretical basis and practical guidance for enterprises to scientifically and effectively promote employees to achieve high performance.